1993
DOI: 10.1108/eb010606
|View full text |Cite
|
Sign up to set email alerts
|

The Glass Ceiling: Women and Mentoring in Management and Business

Abstract: In the beginning, organisations were exceedingly simple. There were chiefs and tribes, or kings and subjects or owners and tenants or bosses and workers. With the advent of the Industrial Revolution, it got more compli‐cated. There were stockholders, board of directors, of‐ficers and employees. Now it is too complicated ‐ with stakeholders and/or, shareholders, chairman of the boards and/or chief executives, corporate presidents and/or chief operating officers, assorted vice presidents, managers and employees.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

1996
1996
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 8 publications
0
19
0
Order By: Relevance
“…In the race to the top, mentors can make the difference between getting on the inside track and trailing the field (Dreher & Ash, 1990;Fagenson, 1989;Scandura & Williams, 2002;Scandura & Hamilton, 2002;Whitely, Dougherty & Dreher, 1991). A number of studies indicate that persons who have received extensive mentoring report that they are promoted more often, earn higher incomes and are more satisfied with pay and benefits (Akande, 1994;Hall & Kahn, 2002;Parsloe & Wray, 2000;Scandura & Hamilton, 2002). So too, research consistently indicates that mentoring is related to a variety of positive work outcomes, including higher degrees of career and organisational commitment, recognition, satisfaction, career mobility and compensation (Fagenson, 1989;Greenhaus et al, 2001;Klasen & Clutterbuck, 2002;Whitely et al, 1991).…”
Section: Women and Mentoringmentioning
confidence: 99%
See 2 more Smart Citations
“…In the race to the top, mentors can make the difference between getting on the inside track and trailing the field (Dreher & Ash, 1990;Fagenson, 1989;Scandura & Williams, 2002;Scandura & Hamilton, 2002;Whitely, Dougherty & Dreher, 1991). A number of studies indicate that persons who have received extensive mentoring report that they are promoted more often, earn higher incomes and are more satisfied with pay and benefits (Akande, 1994;Hall & Kahn, 2002;Parsloe & Wray, 2000;Scandura & Hamilton, 2002). So too, research consistently indicates that mentoring is related to a variety of positive work outcomes, including higher degrees of career and organisational commitment, recognition, satisfaction, career mobility and compensation (Fagenson, 1989;Greenhaus et al, 2001;Klasen & Clutterbuck, 2002;Whitely et al, 1991).…”
Section: Women and Mentoringmentioning
confidence: 99%
“…Paradoxically, mentoring for women has not occurred to a sufficient degree in the workplace, and female employees often find themselves restrained by a number of barriers (Akande, 1994;Clutterbuck & Ragins, 2002). The following barriers have been identified through various studies: women lack access to networks within organisations; women may be viewed as tokens who cannot reach top management; and misconceptions about women's abilities to manage may reduce the view of their performances.…”
Section: Women and Mentoringmentioning
confidence: 99%
See 1 more Smart Citation
“…Managers are mostly engaged in problems' shooting. This culture puts high demands on the top manager to be very knowledgeable and to be able to sort out problems of any kind at all times (Akande 1994;Arnolds and Boshoff 2003;Cuypers and Xavier 2010;Mangaliso 2001).…”
Section: H7: South African Managers Expect To Gain Managerial Controlmentioning
confidence: 99%
“…In addition to its commercial importance experts on cross-cultural research in South (Africa), Akande (1991aAkande ( , 1991bAkande ( , 1994, Akande and Odewale (1994) advised on the advantages of conducting research in South Africa. They suggested that the rapid changes that take place in South Africa pose challenges for the researcher but also offer unparallel opportunities in undertaking cross-cultural studies or international perspectives on management.…”
Section: Introductionmentioning
confidence: 99%